(untitled) (Architecture Image Studies, 2025)
One of the dying performing arts in Malaysia is the Teochew Metal Rod Puppetry, a form of Chinese puppetry. Popular in Malaysia and Singapore in the past decades, puppetry art is the next victim of contemporary entertainment. Unfortunately, there is very little performance group who still perform the ancient art and attempt to preserve it. This study addresses the reasons behind the decline in popularity among Malaysian Chinese particularly the younger generation. The experi-mental study approach has been applied to test the hypotheses. Students from Universiti Tunku Abdul Rahman Sungai Long Campus were invited to experience the dying art form through a Teochew puppetry workshop conducted by the Kim Giak Low Choon Troupe. The primary finding shows that there are prominent factors that contribute to the loss of identity of the youth towards the art form such as detachment of the art form with the current entertainment and the hard time in understanding the context of the performance. The results also showed the implementation of the new technology to help rejuvenate the per-forming art and make it relevant to the younger generation. Technology integration into traditional performing art with the purpose of rejuvenation helps to give traditional art a new sense of breath without affecting its original form. To keep traditional performing arts such as Teochew Metal Rod Puppetry in Malaysia relevant, a proactive action from government, and performers need to be taken to let it stay in our Chinese community so that our future generation can enjoy it.